Welfare Policy and Electoral Preferences: Public Perceptions of the MBG Program in Daerah Istimewa Yogyakarta - Ach. Fawaidi; Ambaristi Hersita Milanguni; Muhammad Khoirul Rizal M (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2026)
This study examines public perceptions of the Makan Bergizi Gratis (MBG) program in the Special Region of Yogyakarta in the context of the 2029 General Election. Using a quantitative survey of 200 student respondents selected through purposive sampling, the study measures three dimensions, namely perceived benefits, targeting accuracy, and political relevance. The findings reveal substantial public scepticism toward the program. A majority of respondents question its effectiveness, 67.5% express doubt about its benefits, and 70% perceive the program as inaccurately targeted. In addition, 65% of respondents associate the program with political interests, particularly in image-building and electoral mobilisation. These results indicate that their functional performance does not solely shape perceptions of welfare policies, but is also shaped by the broader political context in which they are implemented. The study argues that implementation shortcomings, especially in targeting and distribution, contribute to the politicisation of welfare programs. By shifting the analytical focus from voting behaviour to perception as a socio-political construct, this study contributes to the development of political perception theory within welfare politics. It demonstrates that, in a developing democracy, welfare policies are interpreted as political signals rather than purely social interventions.